Attitude towards scientific research in peruvian students of pedagogical higher education - Estrada Araoz, Edwin Gustavo (2021)
The present research aimed to describe the attitudes towards scientific research of the students of the Education career of a pedagogical higher education institute of Madre de Dios, Peru. The research approach was quantitative, the design was non-experimental while the type was descriptive, transactional. 138 students participated to whom a sociodemographic data sheet and the Index of Attitude towards Research were applied, an instrument with the required validity and reliability. According to the findings, the students were characterized by having an unfavorable attitude towards scientific research and it was determined that some sociodemographic variables such as sex and age group were significantly associated with the attitude towards scientific research (p <0.05). Finally, it was concluded that it is necessary to promote the development of didactics and research competencies of the teacher trainers who teach the research course so that the attitude of the students towards said course is more appropriate.